Sistem Pendukung Keputusan Penerima Kartu Indonesia Pintar (KIP) Menggunakan Analisis Metode MOORA dan MOOSRA - Prayogo, M. Ari; Jundillah, Muhammad Labib; Fahrullah, Fahrullah; Rosita, Dewi; Alimyaningtias, Wahyu Nur; Adhari, Vika Aidila; Rifkiansyah, Muhammad (Forum Kerjasama Pendidikan Tinggi, 2024)
The decision-making process is important to improve efficiency and accuracy, especially in assistance programs such as the Smart Indonesia Card (KIP). The problem in this study is that the selection process often faces several obstacles, such as inappropriate targets and subjectivity in decision-making. Therefore, a system is needed that can help decision-making more objectively, transparently, and efficiently. Decision Support Systems (DSS) are one solution that can be used to overcome these problems. This study aims to create a DSS in determining eligible KIP recipients, using two multi-criteria analysis methods, namely MOORA (Multi-Objective Optimization by Ratio Analysis) and MOOSRA (Multi-Objective Optimization on the basis of Simple Ratio Analysis). Analysis using the MOORA and MOOSRA methods in determining prospective students receiving the Smart Indonesia Card (KIP) was carried out using 7 alternatives and 9 criteria. This system is designed by considering criteria such as parental dependents, place of residence, type of house, average report card grades, father's education, mother's education, father's occupation, mother's occupation, and parents' income. The results of the study show that based on the analysis of the calculation of the MOORA and MOOSRA methods, the ranking results were obtained with A5 or Zaysa as alternative students who are entitled to receive KIP among other alternative students. The results of the analysis show that both methods provide consistent results in identifying students who are most entitled to receive KIP assistance. As a recommendation, this system can be further developed in the form of a web-based or mobile application to facilitate implementation and expand the scope of its use.